Magnetic properties of Hf-177 and Hf-180 in the strong-coupling deformed model - Muto, S; Stone, N; Bingham, C; Stone, JR; Walker, P; Audi, G; Gaulard, C; Koester, U; Nikolov, J; Nishimura, K; Ohtsubo, T; Podolyak, Z; et al. (American Physical Society, 2014)
This paper reports NMR measurements of the magnetic dipole moments of two high-K isomers, the 37/2-, 51.4 m, 2740 keV state in Hf177 and the 8-, 5.5 h, 1142 keV state in Hf180 by the method of on-line nuclear orientation. Also included are results on the angular distributions of γ transitions in the decay of the Hf177 isotope. These yield high precision E2/M1 multipole mixing ratios for transitions in bands built on the 23/2+, 1.1 s, isomer at 1315 keV and on the 9/2+, 0.663 ns, isomer at 321 keV. The new results are discussed in the light of the recently reported finding of systematic dependence of the behavior of the gR parameter upon the quasiproton and quasineutron make up of high-K isomeric states in this region. © 2014 American Physical Society.